2017
DOI: 10.1007/s11157-017-9435-0
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics of microbial and viral life in terrestrial geothermal environments

Abstract: Geothermally heated regions of Earth, such as terrestrial volcanic areas (fumaroles, hot springs, and geysers) and deep-sea hydrothermal vents, represent a variety of different environments populated by extremophilic archaeal and bacterial microorganisms. Since most of these microbes thriving in such harsh biotopes, they are often recalcitrant to cultivation; therefore, ecological, physiological and phylogenetic studies of these microbial populations have been hampered for a long time. More recently, culture-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 173 publications
(251 reference statements)
1
21
0
Order By: Relevance
“…Due to constant high temperatures, often associated with high acidity, hot springs have been shown to harbor unique consortia of thermophilic bacteria and archaea [ 2 ]. Hot spring virus communities, while having received attention in recent years, have been limited to only a few thermal springs, mainly sampled from Yellowstone National Park in the United States [ 3 , 4 , 5 , 6 , 7 ]. The majority of these reported virus community analyses were conducted in boiling, acidic springs (between ca.…”
Section: Introductionmentioning
confidence: 99%
“…Due to constant high temperatures, often associated with high acidity, hot springs have been shown to harbor unique consortia of thermophilic bacteria and archaea [ 2 ]. Hot spring virus communities, while having received attention in recent years, have been limited to only a few thermal springs, mainly sampled from Yellowstone National Park in the United States [ 3 , 4 , 5 , 6 , 7 ]. The majority of these reported virus community analyses were conducted in boiling, acidic springs (between ca.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extremozymes are ideal tools for industrial applications where harsh chemical and physical conditions are encountered. However, the difficulties in cultivating extremophiles severely limit access to this class of biocatalysts, thereby metagenomic approaches are now largely used for extremozyme discovery [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing amounts of metagenomic data and fully sequenced genomes now allow us to systematically explore these microbial communities [ 14 , 18 ], enabling us to investigate the uncultured microbial population, the mechanisms of possible adaptation to biogeochemical cycles, and the lifestyles of extreme organisms, and to discover new extremozymes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in extremophiles has boosted metagenomics studies of extreme environments [12][13][14][15][16], and, more recently, remarkable examples of the discovery of novel extremozymes for industrial applications from sequence-based screenings have been reported [17][18][19].…”
Section: Introductionmentioning
confidence: 99%